Analytical methodology for speciation of arsenic in environmental and biological samples - Burguera, Marcela; Burguera, JoséLuis (Talanta (Oxford), 1997)
A literature search on the speciation of arsenic in environmental and biological samples shows an increasing interest of many researchers in the subject. Because of the low level of arsenic species in real samples, many problems related with its speciation remain unresolved: species instability during sampling, storage and sample treatment, incomplete recovery of all species, matrix interferences, lack of appropriate certified reference materials and of sensitive analytical methods, etc. These aspects are underlined in this paper. The continued development of new analytical procedures pretending to solve some of these problems claim for an up-to-date knowledge of the recent publications. Therefore, this paper pretends to review the latest publications on the chemical speciation of arsenic, emphasizing the increasing activity in the development of accurate and precise analytical methods. In most of the cases, separation and preconcentration is necessary, followed by element-specific detection for sensitivity improvement. Hydride generation following separation procedures (e.g., ion-exchange or high performance liquid chromatography) coupled to atomic absorption or atomic emission detectors proved to have sufficient sensitivity to monitor arsenic exposure, although restricts the analysis to hydride-forming species. Modified procedures including some kind of heating in the presence of highly oxidizing agents have proved successful to completely decompose the arsenic containing compounds to arsenate and so to extend the range of compounds which can be determined by these methods. On-line arrangements have the additional advantage of avoiding excessive sample handling, although some of them involve numerous steps and others are too costly to be recommended for routine use. The analytical figures of merits, specially detection limits are given for most of the methods in order to afford comparison and judge possible applicability. These studies, which have been approached in many different ways, would lead to knowledge that are determinant in the understanding of the cycle of this element in environment and of its physiological and toxicological behavior in the living organisms.